Hubungan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Administrasi Infrastruktur Jaringan Kelas Xll Di SMK Negeri 6 Padang - Fahmi ilhami; Heri Mulyono; Regina Ade Darman (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This study aims to determine whether there is a positive and significant contribution between learning motivation and student learning outcomes in the class XII Network Infrastructure Administration subject at SMK Negeri 6 Padang. This type of research is quantitative using correlational research methods. The population in this study were class XII students of the Department of Computer and Network Engineering at SMK Negeri 6 Padang. The sampling technique used is Simple Random Sampling, which was selected as a sample in this study amounted to 41 students. Based on the results of the study, the coefficient of the contribution of learning motivation and learning outcomes was 20.88%. From the data analysis test, it is known that the data are normal and linear. The test results at a significance level of 0.05 (95% confidence level) obtained the value of tcount = 3.210 and ttable = 2.02 because tcount (3.210) > ttable (2.02). Thus is rejected and is accepted, which means that there is a positive and significant contribution between learning motivation and student learning outcomes in the subject of Network Infrastructure Administration (AIJ) class XII at SMK Negeri 6 Padang. Keywords: contribution, motivation, learning outcomes